Training Legislatif sebagai Upaya Penguatan Kapasitas Legislator Mahasiswa Melalui Pelatihan Legal Drafting pada DPM-KM Universitas Tidar - Bayu Aji, Alan; Alawi, Akhmad Roqi (Jurnal Arba - Multidisiplin Pengabdian Masyarakat, 2026)
This community service program aims to strengthen the legislative capacity of student parliament members through a Legal Drafting training session held at the Legislative Training 1 (TL 1) event organized by the Student Representative Council (DPM-KM) of Universitas Tidar. The activity took place on Sunday, October 26, 2025, at the RW 7 Hall, Potrobangsan Village, North Magelang. The training focused on enhancing participants’ understanding of legal drafting, hierarchy of norms, formulation of legal provisions, and simulation of legislative sessions. The method used included interactive lectures, discussions, case analyses, and drafting simulations based on the provided legal drafting module. The results showed a significant increase in participants’ conceptual and practical competence in drafting organizational regulations. This activity is expected to improve the governance and quality of regulatory products produced by the student legislative body.